Transesophageal echocardiography evaluation of tricuspid and pulmonic valves - Aneeta Bhatia (Annals of Cardiac Anaesthesia, 2016)
The tricuspid is the lost valve and the pulmonary being the most anterior, is not visualized well on TEE; The Pulmonary valve is a semilunar valve that separates the right ventricle from the pulmonary artery. It is situated anterior and superior to the aortic valve, almost at right angle to the aortic valve and parallel to the beam of the ultrasound.